Los impuestos diferidos a partir del tratamiento contable de los activos biológicos de la empresa camaronera Mardios S.A. - Pin Carrion, Danny Jesus; Valarezo Cruz, Cristhian Miguel (Universidad Técnica de Machala, 2022)
The objective of the titling work is to analyze the accounting treatment of biological assets in the determination of deferred taxes, based on what is stated in the current accounting and tax regulations, in order to correctly apply it in the accounting process of the shrimp farm Mardios S.A. which is located in the Sta. Rosa canton, province of El Oro, its economic activity is the production and industrialization of shrimp. The application of accounting standards IAS 41 is very important, the lack of knowledge of the correct application in the measurement of biological assets that at the end of the financial year have not been harvested creates inconsistencies by generating unreasonable data. The research is of a quantitative approach, which is a scientific procedure that accesses to measure, count, compare and evaluate the application of deferred taxes in the company, in mention, the research is descriptive, as a research technique the surveys were applied, a booklet with 28 questions was developed in relation to the proposed objectives and the variables, the population was defined in the 7 managers of the accounting department of the shrimp company Mardios S.A. The survey was also applied to 60 experts who work with shrimp companies dedicated to shrimp production.
El objetivo del trabajo de titulación es analizar el tratamiento contable de los activos biológicos en la determinación de impuestos diferidos, con base en lo que expone la normativa contable y tributaria vigente, con el fin de correcta aplicación en el proceso contable de la camaronera Mardios S.A. que se encuentra ubicada en el cantón Sta. Rosa, provincia de El Oro su actividad económica es la producción e industrialización del camarón. Es de mucha importancia la aplicación de las normativas contables NIC 41, el desconocimiento de la aplicación correcta en la medición de los activos biológicos que al final del ejercicio económico no han sido cosechados crean inconsistencias al generar datos no razonables. La investigación es de un enfoque cuantitativo, que es procedimiento científico que accede a medir, contar, comparar y evaluar la aplicación de los impuestos diferidos en la empresa, en mención, la investigación es de tipo descriptiva, como técnica de investigación se aplicó las encuestas, se desarrolló una cartilla con 28 preguntas con relación a los objetivos planteados y las variables, la población se definió en los 7 encargados del departamento contable de la empresa camaronera Mardios S.A. también se aplicó la encuesta a 60 expertos que laboran con empresas camaroneras dedicadas a la producción de camarón.
Keywords: IMPUESTOS DIFERIDOS; TRATAMIENTO CONTABLE; ACTIVOS BIOLOGICOS